2012
DOI: 10.1007/s10194-012-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral medullary ischemic infarction causing autonomic dysfunction and headache: a case report

Abstract: Stroke can present, among other signs, with headache. Here, we describe the case of a man suffering from severe orbitary pain and autonomic dysfunction secondary to dorsolateral medullary ischemia. The anatomical relationship between lesion and symptomatology could be an indirect sign of hypothalamospinal tract involvement in the genesis of autonomic dysfunction and headache resembling a trigeminal autonomic cephalalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In view of the clinical similarity, although no infarction was demonstrated, ischemia of the spinothalamic tract may have also been involved in our case. In addition, facial pain without TN-like features has been described in other cases of lateral medullary infarction without IVAD [ 13 , 14 ]. Moreover, Kuwabara and Hirayama [ 15 ] reported that “eye-to-forehead headache” was present in 1 of 34 patients with lateral medullary infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the clinical similarity, although no infarction was demonstrated, ischemia of the spinothalamic tract may have also been involved in our case. In addition, facial pain without TN-like features has been described in other cases of lateral medullary infarction without IVAD [ 13 , 14 ]. Moreover, Kuwabara and Hirayama [ 15 ] reported that “eye-to-forehead headache” was present in 1 of 34 patients with lateral medullary infarction.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the authors assumed that ischemia of the spinothalamic tract induced the pain. Based on other case reports of facial pain without the features of trigeminal neuralgia in patients with lateral medullary infarction and without vertebral artery dissection, [13,14] ischemic lesions of the spinothalamic tract are presumably related to facial pain. Accordingly, if the MRA of a patient with abrupt facial pain shows signs of IVAD even without lateral medullary infarction, ischemia of the spinothalamic tract should be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Huynh et al reported a case of lateral medullary infarction presenting with presyncope in which autonomic testing showed impaired sympathetic and parasympathetic cardiovascular reflexes 4. Altavilla et al described a case of dorsolateral medullary infarction associated with orthostatic hypotension and trigeminal autonomic cephalalgia 5. Pascual and colleagues described another case presenting with cluster-like headache 6.…”
Section: Descriptionmentioning
confidence: 99%